Effects of Astaxanthin Supplement on Cardiovascular Health: A Systematic Review and Meta-Analysis - Liu, Yongjie; Mo, Wenyue; Ye, Huaqiang; Bao, Meihua; Long, Zhen; Kou, Ruirui; Qiao, Peiyao; Meng, Ruilong; Chen, Ruizhu; He, Rui; Du, Le; Gao, Xinzheng (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: The objective of this study was to evaluate the effects of astaxanthin intake on the cardiovascular disease-related indicators. Materials and Methods: Fives databases, including PUBMED, CNKI, WEIPU, WAN FANG and Clinical Trials were searched up to June 30, 2023. The random-effects model was used to calculate the summary risk. A total of 17 studies were included in this meta-analysis and a total of 1101 subjects' data were included in the analysis. In all included literature studies, a randomly assigned placebo group was established as the control. In the literature included, the average intervention dose of ASTX in the experimental group was 10.14 mg/day, with an average duration of administration of 68 days. Results: The overall study did not show a significant association between Astaxanthin (ASTX) and Systolic Blood Pressure (SBP) (standardized mean difference, SMD: -0.03, 95% CI: -0.22 to 0.17, p=0.771), Diastolic Blood Pressure (DBP) (SMD: -0.16, 95% CI: -0.35 to 0.03, p=0.100), the glucose concentration (SMD: -0.12, 95% CI: -0.39 to 0.15, p=0.398) and Body Mass Index (BMI) (SMD: -0.02, 95% CI: -0.22 to 0.18, p=0.821). However, the results revealed that astaxanthin can significantly reduce total cholesterol concentration (SMD: -0.20, 95% CI: -0.37 to -0.04, p=0.000), low-density lipoprotein cholesterol concentration (LDL-C) (SMD: -0.25, 95% CI: -0.41 to -0.09, p=0.003) and triglyceride concentration (SMD: -0.17, 95% CI: -0.32 to -0.01, p=0.033). Furthermore, astaxanthin could increase the concentrations of high-density lipoprotein cholesterol (HDL-C) (SMD: 0.18, 95% CI: 0.05 to 0.32, p=0.008). Conclusion: The results of this meta-analysis indicate that astaxanthin intake can significantly improve hyperlipidemia. Further studies are needed to validate these findings and investigate the potential cardiovascular benefits of astaxanthin.
Keywords: Astaxanthin; Cardiovascular Health; Efficacy; Hyperlipidemia; Meta-Analysis